Amotekun Corps: Constitutionality or Otherwise as a Subnational Response to Security in a Federal State - Olusegun Femi Akeredolu (Journal of Indonesian Constitutional Law, 2025)
The government exists essentially to secure the welfare and safety of its people. In a modern democratic society like Nigeria, this duty is constitutionally anchored but practically challenged by the over-centralization of security control in the federal government. The recurring insecurity across the country has therefore rekindled the debate on the need for a decentralised security framework that reflects the spirit of federalism. This study aims to examine the constitutional validity of subnational security structures and the legality of law enacted by the State House of Assembly in response to security challenges within the State, particularly the Amotekun Corps, as a model for security federalism in Nigeria. It specifically seeks to determine (i) whether Amotekun violates section 214(1) of the Constitution; (ii) how sections 11(2) and 14(2)(b) provide legal grounds for its existence; and (iii) what framework can reconcile subnational security initiatives with federal authority. The study adopts a doctrinal research method, relying on statutes, judicial authorities, and scholarly writings, with particular attention to the legal foundation and operation of the Ondo State Security Network Agency (Amotekun Corps). It argues that security federalism, properly structured within constitutional limits, will promote efficiency, accountability, and community participation in policing. The study contributes to the growing discourse on federal reform in Nigeria by offering a normative framework for balancing national security with sub-national responsibility through shared constitutional authority.